Voltage-controlled topological interface states for bending waves in soft dielectric phononic crystal plates. (25th December 2022) - Chen, Yingjie; Wu, Bin; Destrade, Michel; Chen, Weiqiu
Abstract: The operating frequency range of passive topological phononic crystals is generally fixed and narrow, limiting their practical applications. To overcome this difficulty, here we design and investigate a one-dimensional soft dielectric phononic crystal (PC) plate system with actively tunable topological interface states via the mechanical and electric loads. We use nonlinear electroelasticity theory and linearized incremental theory to derive the governing equations. First we determine the nonlinear static response of the soft dielectric PC plate subjected to a combination of axial force and electric voltage. Then we study the motion of superimposed incremental bending waves. By adopting the Spectral Element Method, we obtain the dispersion relation for the infinite PC plate and the transmission coefficient for the finite PC plate waveguide. Numerical results show that the low-frequency topological interface state exists at the interface of the finite phononic plate waveguide with two topologically different elements. By simply adjusting the axial force or the electric voltage, an increase or decrease in the frequency of the topological interface state can be realized. Furthermore, applying the electric voltage separately on different elements of the PC plate waveguide is a flexible and smart method to tune the topological interface state in a wide range. These results provide guidance for designing soft smart wave devices with low-frequency tunable topological interface states. Graphical abstract: Highlights: Electromechanically tunable low-frequency topological interface states (TISs). Analytical acoustic characteristics for bending waves in soft dielectric PC plates. A flexible and smart method to tune the TISs by applying electric voltages. Design of tunable TISs in a wide frequency range by the topological phase diagram.